Nanofence Stabilized Platinum Nanoparticles Catalyst via Facet‐Selective Atomic Layer Deposition. Issue 32 (28th June 2017) - Cao, Kun; Shi, Lu; Gong, Miao; Cai, Jiaming; Liu, Xiao; Chu, Shengqi; Lang, Yun; Shan, Bin; Chen, Rong
Abstract : A facet‐selective atomic layer deposition method is developed to fabricate oxide nanofence structure to stabilize Pt nanoparticles. CeO x is selectively deposited on Pt nanoparticles' (111) facets and naturally exposes Pt (100) facets. The facet selectivity is realized through different binding energies of Ce precursor fragments chemisorbed on Pt (111) and Pt (100), which is supported by in situ mass gain experiment and corroborated by density functional theory simulations. Such nanofence structure not only has exposed Pt active facets for carbon monoxide oxidation but also forms ceria–metal interfaces that are beneficial for activity enhancement. The composite catalysts show excellent sintering resistance up to 700 °C calcination. CeO x anchors Pt nanoparticles with a strong metal oxide interaction, and nanofence structure around Pt nanoparticles provides physical blocking that suppresses particles migration. The study reveals that forming oxide nanofence structure to encapsulate precious metal nanoparticles is an effective way to simultaneously enhance catalytic activity and thermal stability. Abstract : Nanofence cerium oxide structure coated Pt nanoparticles are synthesized via facet‐selective atomic layer deposition, the nanofence structure stabilizes metal nanoparticles, and simultaneously enhances catalytic activity toward carbon monoxide oxidation.